Pengukuran dan Analisis Kinerja Laboratorium Kalibrasi Untuk Meningkatkan Daya Saing Perusahaan - Dita Indah Rahmawati; Evi Yuliawati (Politeknik ATI Padang, 2022)
Calibration Laboratory PT. ABC is one of the calibration specialist laboratories, offering calibration service facilities and tool sales via a job order system under the warranty and ISO departments. Currently, performance measurement in the Calibration Laboratory is based on incoming order targets being met by the warranty and ISO departments. This method of measuring performance cannot be used as a benchmark. As a result, the Calibration Laboratory must implement an adequate performance measuring method to determine whether or not the company's performance has been satisfactory. This study uses the Sink's Seven Performance Criteria technique to assess firm performance based on seven criteria: productivity, effectiveness, efficiency, quality, profitability, work life, and innovation. The performance measurement results obtained using this method can identify 23 Key Performance Indicators (KPI) at PT. ABC's Calibration Laboratory (Persero). The use of a scoring system based on the Objective Matrix (OiMAX) and the Traffic Light System is known to obtain a performance index of 7.78 for the Calibration Laboratory of PT. ABC in 2021. According to the Traffic Light System, Calibration Laboratory's total performance value is in the yellow category, indicating that average performance has also not met the aim. Management must strive harder to improve its performance by selecting criteria that are poor and have a high weight. They are then assessed and suggestions for improvement are made using Fishbone diagrams and 5W+1H.